Neurotransmitters, Cell Types, and Circuit Mechanisms of Motor Skill Learning and Clinical Applications - Tian, Wotu; Chen, Shengdi (Frontiers in Neurology, 2021)
Animals acquire motor skills to better survive and adapt to a changing environment. The ability to learn novel motor actions without disturbing learned ones is essential to maintain a broad motor repertoire. During motor learning, the brain makes a series of adjustments to develop new sensory-motor relationships that are stored in specific circuits and retained for extended periods. How the brain learns new motor actions and transforms them into long-term memory remains elusive. Here we review the latest findings with regard to the contributions of various brain subregions, cell types, and neurotransmitters to motor learning. Aiming to seek therapeutic strategies to restore the motor memory in relative neurodegenerative disorders, we also briefly describe the common experimental tests and manipulations for motor memory in rodents.